Contact entre patois et français en Suisse romande de 1800 à 1970 : l’unilinguisme revisité - Dorothée Aquino-Weber; Sara Cotelli Kureth; Christel Nissille (Revue des Langues Romanes)
This article explores the diglossia between Patois and French in French-speaking Switzerland between 1800 and 1970. We examine the contact between these two languages through the analysis of the discourse on regional words and the language ideologies they express. Our diversified corpus (newspapers, cacologies, dictionaries and language columns) allowed us to observe a unified voice on the long term, which accepts regional words under specific conditions. Even in purist discourse, borrowings from Patois are considered a treasure, a testimony of the genius loci, of a particular region. Patois is even called upon to help French, which is considered corrupted by borrowings from German and English.